A comprehensive approach to the treatment of infertility caused by inflammatory diseases of the pelvic organs - I A Lapina; L A Ozolinia; N I Nasyrova; L I Patrushev; Yu E Dobrokhotova; K R Bondarenko (IP Berlin A.V., 2016)
Objective. To develop the tactics of complex treatment of patients with infertility caused by chronic inflammatory diseases of the pelvic organs to improve the quality pregravid stage and reduce the risk of reproductive losses. Materials and methods. 70 patients were operated with chronic inflammation of the pelvic organs, primary or secondary infertility. The study was prospective in nature. All patients were performed complete clinical and laboratory tests, genotyping of the most significant thrombophilic polymorphisms, as well as assessed the vaginal microflora. Conclusions. The tactics of treating the patients with infertility caused by inflammatory diseases of the pelvic organs, should include an individual holistic approach aimed at improving pregravid stage of treatment. In it, in addition to surgical approach, normalization of hemostasis system, preparation of the endometrium, the prevention of exacerbations of bacterial and viral infections should be included.